Psyllium Polysaccharide-Based hydrogels as smart Biomaterials: Review. (2022) - Singh Kaith, Balbir; Rohit,; Kumar, Rakesh
Abstract: Among the various macromolecules used for hydrogel formation, polysaccharides, the naturally existing biopolymers offer sustainable building blocks and considered beneficial compared to synthetic polymers. Polysaccharide-based hydrogels have received a great attention in various applications due to their unique properties like renewability, biocompatibility and biodegradability. Polysaccharides are abundant in nature, renewable, and nontoxic. The polysaccharides-based hydrogels are intensely explored have attracted great interest for various biomedical applications such as drug delivery carriers, cell-encapsulating biomaterials, tissue engineering scaffolds, and water purification devices. The primary objective of this article is to review the literature about the recent developments in psyllium polysaccharide-based hydrogels. This mini review systematically summarizes methods for the preparation of psyllium polysaccharide-based hydrogels along with their swelling behaviour and the latest progress in the multifunctional applications of psyllium polysaccharide-based hydrogels.